CTAB assisted synthesis of ultra-high aspect ratio 3Mg(OH)2·MgCl2·8H2O nanowires. (24th March 2023) - Gong, Lu; Yao, Zhenying; Zhu, Chunmei; Xiang, Lan; Lian, Xin; He, Bai; Fan, Baoyan; Yu, Bo
Abstract : 3Mg(OH)2 ·MgCl2 ·8H2 O nanowires with ultra-high aspect ratios were synthesized by a liquid method, and the effects of cetyltrimethylammonium bromide (CTAB) were investigated. Abstract : In this work, 3Mg(OH)2 ·MgCl2 ·8H2 O (318MHCH) nanowires with ultra-high aspect ratios were first synthesized by a liquid method, and the effects of cetyltrimethylammonium bromide (CTAB) in highly concentrated salt solution were investigated. The structure and morphology of the synthesized 318MHCH nanowires were characterized. The as-prepared 318MHCH nanowires have a typical triclinic structure and relatively good crystallization properties. By introducing CTAB, the aspect ratio of 318MHCH nanowires will significantly increase from 500 to 4000. The high aspect ratio of 318MHCH nanowires is due to the increase in solution viscosity and the selective adsorption of CTAB molecules on the crystal surface. FTIR, Raman and XPS spectroscopy confirmed that the positively charged nitrogen-containing head of the CTAB molecule interacts with the surface of the 318MHCH crystal. Furthermore, since the (−1 0 1) plane has a lower electrostatic potential, the nitrogen-containing head of CTAB with a high potential is more readily adsorbed, which was confirmed by molecular dynamics simulations. Therefore, CTAB is selectively adsorbed on the side of 318MHCH nanowires, hindering the lateral growth and promoting the aspect ratio of 318MHCH nanowires. In addition, other cationic surfactants have been shown to have similar effects on the selective growth of nanowires.